Dried and Tested: Inoculation Method Impacts Low-Moisture Food Persistent Bacterial Populations - Manita Adhikari; Kavita Patil; Jennifer C. Acuff (Journal of Food Protection)
Pathogen contamination and harborage in low-moisture food (LMF) processing environments have resulted in outbreaks and recalls, but researchers are limited in their abilities to investigate solutions. Methods used in most laboratory studies do not accurately reflect the route of contamination or harborage of pathogens in LMF environments, which complicates studying of sanitation methods. Inoculation methods were compared to establish low-moisture food persistent bacterial populations (LMF PBPs) that realistically reflect populations found in LMF environments. Culture-preparation techniques, food matrices, and ratios of nutrient to moisture were compared for their impacts on Salmonella Tennessee survival. A slurry method with 0.5 mL of culture to 0.4 g (NFDM) was easiest to form, inoculate, and process for further investigation, as was more consistent than other methods. With the chosen technique, LMF PBPs of Salmonella Tennessee (0.5: 0.4 [mL Salmonella Tennessee to g Powder]) with different powders (NFDM, peanut butter powder [PB], chicken powder [CP] and silicon dioxide [SiO2]) were made using lawn-based and broth-based cultures and distributed evenly on sterilized stainless-steel coupons to compare the impacts of preparation and food matrix on survival. Coupons stored at 22–25 °C and 50% relative humidity (RH) were assessed on 0, 1, 3, 5, and 7 days. Matrices and culture preparation showed significant differences (p ≤ 0.05). Salmonella LMF PBP derived from bacterial lawns demonstrated higher initial populations (10.1 ± 0.0 log CFU/cm2) compared to the broth cultures (8.2 ± 0.2 log CFU/cm2). Salmonella LMF PBP reductions were lower for the lawn-prepared cultures (0.3–2.7 log CFU/cm2) compared to broth-based cultures (1.0–5.1 log CFU/cm2) for all food matrices. Salmonella in LMF PBP with SiO2 (2.7–5.1 log CFU/cm2) reduced significantly more than in other food matrices (0.7–2.2 log CFU/cm2) and Sal without a matrix (0.3–1.5 log CFU/cm2) for both culturing methods.